New Aspects of Resuscitation in Neurology and Neurosurgery - K. A. Popugaev; I. A. Savin; A. V. Oshorov (Общая реаниматология, 2014)
The course of critical conditions in neurology and neurosurgery has specific features associated with the complex pathogen esis of brain injury, which in turn determines the specificity of resuscitation care. For a brief description, general resuscita tion methods in neurology and neurosurgery should be characterized by the term of neuroresuscitation. The paper presents the latest trends in multimodality monitoring and specific therapy in neuroresuscitation. Furthermore, it gives the data show ing the great importance of infection monitoring for the treatment of critically ill neurological and neurosurgical patients.